Study on seismic response characteristics of the suction bucket group foundation in liquefiable sites - Tao, Xiaosan; Gao, Zhibing (Frontiers in Physics, 2025)
The multi-suction bucket foundation has the potential to enhance anti-overturning capacity by converting the overturning moment of the entire system into axial push-pull forces of individual buckets. In recent years, offshore wind turbines with multi-bucket suction bucket group foundations have been successively put into production and use in China. However, research addressing the seismic dynamic performance of quad-bucket suction foundations embedded in saturated sandy strata remains scarce. Therefore, studying the seismic dynamic response of suction bucket group foundations is of significant practical importance. Based on the finite-element software OpenSees and focusing on the characteristics of liquefiable sites, this paper establishes a numerical model of a four-bucket suction bucket group foundation in saturated sand using an actual engineering project as the background. Considering the effects of earthquake and sand liquefaction, the seismic dynamic response and displacement variations of the four-bucket foundation in liquefiable sites are investigated. The results show that: under seismic action, the peak horizontal displacement of the suction buckets occurs synchronously with the peak ground acceleration; vertical settlement exhibits nonlinear growth with increasing peak ground acceleration, and differential settlement of the foundation is significantly aggravated in liquefiable sites; the excess pore water pressure ratio γu serves as a key index for quantifying soil liquefaction, and when γu ≥1, the soil inside the buckets is completely liquefied, leading to a sudden drop in foundation bearing capacity.